Предмет: Математика,
автор: alovosiem
плизи, ребятки помогите. срочняк.
Приложения:
Ответы
Автор ответа:
0
7^lg(x) - 5^(lg(x) + 1) = 3 * 5^(lg(x) - 1) - 13 * 7^(lg(x) - 1)
7^lg(x) - 5*5^(lg(x)= (3/5) * 5^lg(x) - (13/7) * 7^lg(x)
(20/7) * 7^lg(x) = (28/5) * 5^lg(x)
(5/7)^lg(x) = 25/49
(5/7)^lg(x) = (5/7)^2
lg(x) = 2
x = 100
ОДЗ:
x > 0 - подходит
Ответ: х = 100
7^lg(x) - 5*5^(lg(x)= (3/5) * 5^lg(x) - (13/7) * 7^lg(x)
(20/7) * 7^lg(x) = (28/5) * 5^lg(x)
(5/7)^lg(x) = 25/49
(5/7)^lg(x) = (5/7)^2
lg(x) = 2
x = 100
ОДЗ:
x > 0 - подходит
Ответ: х = 100
Похожие вопросы
Предмет: Математика,
автор: AismailovW
Предмет: Английский язык,
автор: Lovemaybich
Предмет: Литература,
автор: sonyasofiya2009
Предмет: Математика,
автор: nbalischeva
Предмет: Биология,
автор: убачный